2006
DOI: 10.1007/s10812-006-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional potential energy function for internal rotation in 1,2-dihydroxybenzenes

Abstract: We have obtained an analytical expression for the two-dimensional potential energy function for internal rotation in 1,2-dihydroxybenzenes, allowing us to use perturbation theory methods to calculate and interpret the torsional spectra of these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Relatively little work has been published on vibrational PESs outside our laboratory in recent years, although a number of papers have appeared on the study of internal rotations. Several of our recent studies have focused on determining two-dimensional PESs for bicyclic molecules in order to better understand how the two rings interact. We are aware of only one report of a two-dimensional PES from another laboratory . In 2004 we presented our study of bicyclo[3.3.0]oct-1,5-ene (BCO) and showed that its PES could be represented by a function of the form V = a ( x 1 4 + x 2 4 ) + b ( x 1 2 + x 2 2 ) + c x 1 2 x 2 2 + d x 1 x 2 where x 1 and x 2 are the ring-puckering coordinates of the two rings and a , b , c , and d are potential energy parameters that are determined so that they best fit the two different conformational energies and energy barriers found from ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively little work has been published on vibrational PESs outside our laboratory in recent years, although a number of papers have appeared on the study of internal rotations. Several of our recent studies have focused on determining two-dimensional PESs for bicyclic molecules in order to better understand how the two rings interact. We are aware of only one report of a two-dimensional PES from another laboratory . In 2004 we presented our study of bicyclo[3.3.0]oct-1,5-ene (BCO) and showed that its PES could be represented by a function of the form V = a ( x 1 4 + x 2 4 ) + b ( x 1 2 + x 2 2 ) + c x 1 2 x 2 2 + d x 1 x 2 where x 1 and x 2 are the ring-puckering coordinates of the two rings and a , b , c , and d are potential energy parameters that are determined so that they best fit the two different conformational energies and energy barriers found from ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only one report of a twodimensional PES from another laboratory. 16 In 2004 we presented our study of bicyclo[3.3.0]oct-1,5-ene 17 (BCO) and showed that its PES could be represented by a function of the form…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus the contributions of the cross term ∂ 2 ⁄ ∂g 1 ∂g 2 and the first derivatives ∂ ⁄ ∂g 1 and ∂ ⁄ ∂g 2 are small and can then be taken into account by perturbation theory, while the kinetic part of Hamiltonian (2) allows for separation of variables. The potential energy function for internal rotation can be represented in the form [7]:…”
mentioning
confidence: 99%
“…To model the torsional IR and Raman spectra of hydroquinone, the following values were selected for the potential energy function to internal rotation [32]: V 0 = 1100-2000, V 1 = V 3 = 800-1000, V 2 = 1000-1900, V 4 = V 5 = 10-50 cm -1 . One variant of the torsional potential function for hydroquinone is given in Fig.…”
mentioning
confidence: 99%